Pengembangan Bahan Ajar Modul Pembelajaran - Shidqon Famulaqih; Aceng Lukman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The availability of teaching materials can be one of the supporting factors for the success of the learning process. With teaching materials, students can study competencies in a sequential and systematic manner, allowing them to master all competencies thoroughly. One of the teaching materials used by students in the learning process is the module. Based on this, the development of learning modules is considered important for the success of the learning process. Therefore, this research aims to develop and expand the body of knowledge regarding learning module materials, enabling readers to gain a deeper understanding of learning modules. In this article, the author focuses on development objectives using a library research method, meaning the author seeks to deepen and broaden existing knowledge. A learning module is a specially designed teaching material that is systematic and includes instructions containing learning experiences by organizing subject matter, making it possible to be studied independently or with guidance, thus facilitating learners in their studies. Learning modules have several characteristics that are advantageous, including being self-instructional, self-contained, stand-alone, adaptive, and user-friendly. The development of teaching module materials analyzed by the researcher is essential to pursue, both in theoretical and practical studies, as the learning process is dynamic and must keep pace with the times.s.